Evaluation of Information Technology Use in the Quality of Physical Education Sports and Health Learning at MTsN 2 Bengkulu City - Khairiah, Khairiah; Destiana, Eem Merani; Febrianto, Reindo (UIN Fatmawati Sukarno Bengkulu, 2025)
Abstract: The quality of technology-based learning is still difficult to improve because human resources remain weak in terms of device ownership and technology literacy. This study aims to evaluate the use of information technology in improving the learning quality of Physical Education, Sports, and Health (PJOK) at MTsN Kota Bengkulu. A descriptive qualitative method was employed, using the CIPP (Context, Input, Process, Product) approach. Data were collected through observation, interviews, and documentation. The research findings show that the use of information technology in Physical Education, Sports, and Health learning—such as instructional videos, fitness applications, and online learning platforms—can enhance students’ motivation and understanding. The integration of information technology also encourages more collaborative and contextual learning. Most teachers have utilized information technology in the learning process, although several technical challenges remain, such as limited ownership of technological devices, the level of information technology literacy among teachers and students, and the lack of technological infrastructure in madrasahs. Thus, it can be concluded that the use of information technology is capable of improving the quality of Physical Education, Sports, and Health learning in madrasahs. Therefore, it is recommended that to further improve the quality of Physical Education, Sports, and Health learning, the evaluation of information technology use in madrasahs should be strengthened.Keywords: Evaluation of Information Technology Utilization, Quality of Physical Education, Sports, and Health Learning. Abstrak: Mutu pembelajaran berbasis teknologi masih sulit ditingkatkan karena sumberdaya manusia masih lemah pada tingkat kepemilikan perangkat dan literasi teknologi. Penelitian ini bertujuan untuk mengevaluasi penggunaan teknologi informasi dalam meningkatkan mutu pembelajaran Pendidikan Jasmani, Olahraga, dan Kesehatan di MTsN Kota Bengkulu. Menggunakan metode kualitatif deskriptif, pendekatan CIPP (Context, Input, Process, Product). Pengumpulan data melalui observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa penggunaan teknologi informasi dalam pembelajaran Pendidikan Jasmani, Olahraga, dan Kesehatan seperti video pembelajaran, aplikasi kebugaran, dan platform pembelajaran daring dapat meningkatkan motivasi dan pemahaman siswa, integrasi teknologi informasi mendorong pembelajaran yang lebih kolaboratif dan konkstual. Sebagian besar guru telah menggunakan teknologi informasi dalam proses pembelajaran meskipun masih terdapat beberapa kendala teknis, seperti keterbatasan kepemilikan perangkat teknologi, dan tingkat literasi teknologi informasi guru dan siswa, serta minimnya infrastruktur teknologi di madrasah. Dengan demikian dapat disimpulkan bahwa penggunaan teknologi informasi mampu meningkatkan mutu pembelajaran Pendidikan Jasmani, Olahraga, dan Kesehatan di madrasah. Sehingga dapat disarankan untuk meningkatkan mutu pembelajaran Pendidikan Jasmani, Olahraga, dan Kesehatan, maka tingkatkanlah evaluasi penggunaan teknologi informasi di madrasah.Kata kunci: Evaluasi Penggunaan Teknologi Informasi, Mutu Pembelajaran Pendidikan Jasmani, Olahraga, dan Kesehatan.